Fear in the Medical and Literary Imagination, Medieval to Modern Dreadful Passions (Palgrave Studies in Literature, Science and Medicine, 2018)
This book is about an emotion constantly present in human culture and history: fear. It is also a book about literature and medicine, two areas of human endeavour that engage with fear most acutely. The essays in this volume explore fear in various literary and medical manifestations, in the Western World, from medieval to modern times. It is divided into two parts. The first part, Treating Fear, examines fear in medical history, and draws from theology, medicine, philosophy, and psychology, to offer an account of how fear shifts in Western understanding from the Middle Ages to Modern times. The second part, Writing Fear, explores fear as a rhetorical and literary force, offering an account of how it is used and evoked in distinct literary periods and texts. This coherent and fascinating collection will appeal to medical historians, literary critics, cultural theorists, medical humanities' scholars and historians of the emotions.